MEDIA AS THE ALCHEMIST OF SOCIETAL PERCEPTION: NAVIGATING THE COMPLEX MAZE OF INFLUENCE, RESPONSIBILITY, AND NARRATIVE ALCHEMY - Ronald Alfredo; Karnawi Kamar; Adi Mursalin; Iyad Abdallah Al- Shreifeen; Aceng Haetami (Adisam Publisher, 2024)
In the exploration titled